2004
DOI: 10.1111/j.1365-2672.2004.02424.x
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Delta12-oleic acid desaturase gene of a nonaflatoxigenic Aspergillus parasiticus field isolate affects conidiation and sclerotial development

Abstract: Aims: To investigate how linoleic acid affects conidial production and sclerotial development in a strictly mitotic Aspergillus parasiticus field isolate as related to improving biocompetitivity of atoxigenic Aspergillus species. Methods and Results: We disrupted A. parasiticus D12-oleic acid desaturase gene (odeA) responsible for the conversion of oleic acid to linoleic acid. We examined conidiation and sclerotial development of SRRC 2043 and three isogenic mutant strains deleted for the odeA gene (DodeA), ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…The values are in agreement with those supplied in the tables of feed composition and nutritive values in China (2013, 24 edition), in which the fat contents of soybean, corn, and wheat are 17.3-18.7, 3.1-5.3, and 1.7 g/100 g, respectively [28], whereas that of peanut is 48.7 g/100 g [29]. According to Chang et al [30] and Wilson et al [31], oil-rich crops are often infested with toxigenic fungi. Lillehoj et al [32] reported previously that ground, autoclaved corn and full-fat corn germ were excellent substrates, while defatted germ was the poorest substrate for toxin production.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The values are in agreement with those supplied in the tables of feed composition and nutritive values in China (2013, 24 edition), in which the fat contents of soybean, corn, and wheat are 17.3-18.7, 3.1-5.3, and 1.7 g/100 g, respectively [28], whereas that of peanut is 48.7 g/100 g [29]. According to Chang et al [30] and Wilson et al [31], oil-rich crops are often infested with toxigenic fungi. Lillehoj et al [32] reported previously that ground, autoclaved corn and full-fat corn germ were excellent substrates, while defatted germ was the poorest substrate for toxin production.…”
Section: Resultssupporting
confidence: 75%
“…Chang et al [30] and Wilson et al [31] that high-oil crops are often infested with toxigenic fungi. In addition, seed oil mainly consists of fatty acids, such as palmitic acid (C16:0), stearic acid (C18: 0), oleic acid (C18: 1), linoleic acid (C18: 2), and linolenic acids (C18: 3), among which oleic and linoleic acids are the most common unsaturated fatty acids [39][40][41].…”
Section: Effects Of Different Oil Levels On Afb 1 Production By Aspermentioning
confidence: 98%
“…It was consequently defective in rates of spore germination, colony growth and development. In a parallel study, a DodeA mutation that was generated in an Omethylsterigmatocystin-accumulating strain of A. parasiticus, SRRC 2043, also resulted in altered conidiation and sclerotial development (Chang et al, 2004). This supports our conclusion that the reduction in conidiation and abolishment of sclerotial production seen for DApodeA compared to the wild-type is due solely to aberrant polyunsaturated fatty acid metabolism and serves to emphasize the genetic connection between fatty acid metabolism and fungal development.…”
Section: Discussionsupporting
confidence: 74%
“…The fatty acid composition of sexual tissues of Neurospora differs substantially from the composition of asexual tissues, such changes in fatty acid composition correlate with the sexual stage of development, and mutations in the gene encoding the b-fatty acid synthase affect sexual development (GoodrichTanrikulu et al 1998). Precocious sexual inducers (psi factors), a family of structurally related oleic-and linoleic-acid-derived oxylipins, have been shown to alter the ratio of asexual to sexual sporulation in the filamentous fungus A. nidulans (Calvo et al 2001;Chang et al 2004;Tsitsigiannis et al 2005). It is also known that the formation of lipid bodies increases in saprophytic fungi with the formation of reproductive structures (Losel and Sancholle 1996).…”
Section: Discussionmentioning
confidence: 98%